Комплекси міцел поверхнево-активних речовин з полімерами у водних рідинних системах - Artykulnyi, O. P.; Petrenko, V. I.; Avdeev, M. V.; Bulavin, L. A. (Publishing house "Academperiodika", 2020)
Researches on the structural self-organization and aggregation in aqueous liquid systems of surfactants and polymers have been reviewed. Main attention is focused on the results obtained for the interaction of ionic surfactants with non-ionic polymers. Capabilities of the small-angle neutron scattering and neutron reflectometry methods for the study of the micellar structure, micelle-polymer aggregates, and complex multicomponent systems with nanoparticles are considered. Brief information is provided on some complementary methods used for the structural analysis of liquid systems with self-organization.